Mediation as a potentiating agent of dissemination in Archives: experience of the Arquivo nosso de cada dia campaign - Sousa, Antonio Gouveia de [UNESP]; Ribas, Elisabete Marin [UNESP]; Arantes, Flavio Ricci; Vitoriano, Marcia Cristina de Carvalho Pazin [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2023)
Information mediation, as well as cultural mediation, in Information Science, and especially in Archival Science, are themes that demand further theoretical and methodological inquires. This paper ponders over the importance of mediation in the context of content dissemination activities oriented to the magnification of the social representation of archives. To this end we take as case study the Arquivo nosso de cada dia [Our daily archive], campaign of the Public Archive of the State of Sao Paulo, with the goal of encouraging critical thinking about the importance of the mediation process in dissemination activities of archival institutions. This paper has a qualitative, quantitative, descriptive and exploratory approach, and employs as methods the analysis of the documents generated during the campaign. The results prove how important it is to archival institutions to carry out actions of mediated promotion directed to different social groups that directly affect the way how society sees and welcome these spaces of memory.
Keywords: information mediation; cultural mediation; mediated promotion; diffusion in archival institutions; our daily archive